Synthesizing ZnMn2O4 onto Commercial Microsilica (Caposil - CAP) in the Presence of Tannic Acid (TA) for Enhancing Photocatalytical Degradation of Methylene Blue (MB) - Hoang, Do Huy; Nguyet, Trieu Thi; Tuan, Nguyen Quoc (VNU Journal of Science: Natural Sciences and Technology; Vol 42 No 2DO - 10.25073/2588-1140/vnunst.5879, 2026)
Spinel-based materials ZnMn 2 O 4 (ZMO), ZMO/CAP, and ZMO/CAP@TA were successfully synthesized using a simple technique. The obtained products were characterized by XRD, IR, and SEM methods. The results indicated that the crystalline phase of all materials was purely spinel, with ZMO/CAP and ZMO/CAP@TA exhibiting smaller and more uniform particle sizes compared to ZMO. All synthesized materials demonstrated the ability to decolorize Methylene blue (MB), among which ZMO/CAP@TA showed the highest degradation efficiency, reaching over 90% after 300 minutes under typical conditions, including compact lamp illumination, neutral pH, and room temperature. The material also exhibited good reusability, maintaining a decolorization efficiency of 54% after five cycles. Furthermore, ZMO/CAP@TA demonstrated the ability to degrade Ciprofloxacin with an efficiency of up to 85% after 300 minutes, indicating its potential as a catalyst for the degradation of both dyes and antibiotics in aqueous environments.